2023
DOI: 10.1038/s41598-023-28794-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and characterization of Bambara groundnut [Vigna subterranea (L.) verdc.] accessions under multi-environments considering yield and yield components performance

Abstract: Bambara groundnut has significant role to play in terms of food security, even though researchers in agriculture have paid very little attention to the crop in the past. This study aimed to investigate the high-yielding accessions in three environments. A total of 34 phenological, vegetative and yield traits were measured and analyzed statistically with R software. There were significant differences in all the traits except for plant height, initial plant stand, panicle length per stem, and petiole length. Acr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
1
0
0
Order By: Relevance
“…The analysis of 'locations' showed significant variations for 20 out of the 28 traits evaluated in the years. A similar result was obtained by Esan et al (2023) who reported significant differences in traits of Bambara groundnut evaluated in different regions in Cote d'Ivoire. Yield per plant varied significantly among accessions in the years from 12 to 42 g/plant, indicating that the yield of Bambara groundnut varied widely depending on accessions and environmental conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The analysis of 'locations' showed significant variations for 20 out of the 28 traits evaluated in the years. A similar result was obtained by Esan et al (2023) who reported significant differences in traits of Bambara groundnut evaluated in different regions in Cote d'Ivoire. Yield per plant varied significantly among accessions in the years from 12 to 42 g/plant, indicating that the yield of Bambara groundnut varied widely depending on accessions and environmental conditions.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, another study by [16] to explore the production and utilization of Bambara groundnut in Uganda found that variation exists among different Bambara groundnut landraces in terms of plant growth and development with advance days after germination. [17] also reported similar results from their study on Genetic dissimilarity and classification of Bambara groundnut accessions under environments considering yield and yieldrelated traits. Mean plant heights did not show any significant difference among all the landraces used in this study except at two weeks and ten weeks after planting which showed significant variation among the landraces used (Table 3).…”
Section: Resultssupporting
confidence: 65%
“…The study also showed a negatively significant correlation between the date of maturity and the number of pods per plant (r = -0.05). Esan et al (2023) found significant positive correlations for most of the traits evaluated in Nigerian landraces.…”
Section: Correlation Analysismentioning
confidence: 82%
“…Similarly, Gerrano et al (2013) and Siwale et al (2022) reported the existence of phenotypic variation among diverse Bambara groundnut accessions in South Africa. Moreover, a study that was conducted in Nigeria also reported the presence of phenotypic variation among tested Bambara groundnut landraces (Esan, Oke & Ogunbode 2023). Zongo et al (2023) also reported significant differences among the Bambara groundnut genotypes in Niger.…”
Section: Agro-morphological Variabilitymentioning
confidence: 89%